2018
DOI: 10.1007/s00384-018-3062-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability and feasibility of structured, routine collection of comorbidity data in a colorectal cancer multi-disciplinary team (MDT) setting

Abstract: PurposeAvailability of comorbidity assessment at multi-disciplinary team (MDT) discussions is cornerstone in making the MDT process more robust and decisive in optimising treatment and improving quality of survivorship. Comorbidity assessments using tools, such as the ACE-27 questionnaire would aid in optimising the decision-making process at MDTs so that treatment decisions can be made without delay. This study determined the availability of comorbidity data in a CRC MDT and the feasibility of routine comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…A comprehensive case presentation requires a structured and condensed provision of relevant medical information on the diagnostic path, including information on symptoms, biomarker measures, imaging results, pathology, tumor stage and definition of treatment-related considerations. Presentation of patient characteristics should efficiently capture the essence of risk factors, performance status, information on relevant comorbidities and available information on patient preferences [ 19 , 20 , 21 ]. Though many MDT teams have performed targeted quality improvement work related to, e.g., referral guidelines, meeting structure and case discussion format, there is a lack of guidelines on which data elements should be provided for a comprehensive MDT case discussion.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive case presentation requires a structured and condensed provision of relevant medical information on the diagnostic path, including information on symptoms, biomarker measures, imaging results, pathology, tumor stage and definition of treatment-related considerations. Presentation of patient characteristics should efficiently capture the essence of risk factors, performance status, information on relevant comorbidities and available information on patient preferences [ 19 , 20 , 21 ]. Though many MDT teams have performed targeted quality improvement work related to, e.g., referral guidelines, meeting structure and case discussion format, there is a lack of guidelines on which data elements should be provided for a comprehensive MDT case discussion.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have evaluated and reported the responses of lung cancer MDT members to data presentation and feedback using a mixed‐methods approach. Several studies investigate aspects of MDT practice (from lung cancer and other streams), including processes, reporting to general practitioners, data characteristics, and timing of MDT discussion . The systematic review by Prades et al includes three papers that focus on aspects of lung cancer MDT care.…”
Section: Discussionmentioning
confidence: 99%
“…From studies involving other tumor streams, a UK study of comorbidity data collection by a single‐center colorectal cancer MDT showed a marked improvement with the introduction of routine ACE‐27 index calculation in surgical clinics prior to the MDT (increasing from 54% to 100% comorbidity data availability post‐intervention). A UK observational study of serial breast cancer MDT meetings in a single center identified higher quality biomedical information (history, radiology, and pathology) compared with patient‐related information (psychosocial, comorbidities, and patient views) as scored by the previously published MDT‐MODe assessment tool .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that some data (such as comorbidity) are not being recorded consistently by MDTs across the medical and surgical specialties . Use of a checklist and ground rules made clear before every MDT and perhaps circulated via email or on the previous MDT list might improve this process.…”
Section: How Can We Improve Human Factors Awareness At An Mdt?mentioning
confidence: 99%